Internationalisation of the Aragon Inspectorate: Erasmus+ accreditation 2024–2027 - Castillo Antoñanzas, Encarnación; Carcelén Fernández, Nieves; Gascón Villarig, José Javier (Avances en Supervisión Educativa, 2026)
This article outlines the internationalisation process undertaken by the Aragon Education Inspectorate since 2023, which culminated in the award of its first Erasmus+ accreditation (KA120-SCH-C646D4A6). This process was initiated in response to one of the objectives set out in the Aragon Education Inspectorate’s professional training and development plan, focusing on issues related to mental health, emotional wellbeing and inclusion. The growing complexity of today’s social challenges has highlighted the need for a broader perspective and proven experience at an international level. This document outlines the work carried out, from the initial concerns through to future prospects, including actions aligned with institutional priorities. The aim is to raise the profile of the projects associated with the accreditation and to encourage other educational teams and services to design similar proposals that contribute to improving the responses offered by the Administration and schools to the challenges of a turbulent and vulnerable society, particularly in the areas of mental health and educational wellbeing. The Inspectorate’s contribution to improving the education system and the quality and equity of teaching is one of its core objectives; this initiative is geared towards that end.
Keywords: Education inspectorate, professional development plan, internationalisation, inclusion, mental health, educational wellbeing